EFFEKTIVITAS TEKNIK PENEBANGAN TERARAH DENGAN BANTUAN TALI DI HUTAN RAKYAT - Hardjanto; Budiaman, Ahmad; Agustin, Sarah (Jurnal Belantara, 2024)
Directional felling is a technique that directs fallen trees in a predetermined direction to minimize damage to residual stands and understory plants and facilitate subsequent stages of timber handling. One of the felling techniques used in private forest harvesting was the rope-assisted directional felling technique. The study aimed to analyze and evaluate the effectiveness of the rope-assisted directional felling technique in private forests. The study was conducted in a private forest managed with an agroforestry system in Probolinggo, East Java. The number of sampled trees was 31 trees. The sampled trees were felled to the predetermined directions: to a stretched rope between two spar trees or the safe area. Felling errors, hang-ups, and the presence of barber chairs were used to assess the effectiveness of the rope-assisted felling technique. The average diameter of the felled trees was 23.4 cm and 20.8 m in height. The ropes-assist directional felling technique produced a hang-up tree of 19.35% of the total felled trees. Directional felling using ropes made fallen trees from close to the opposite direction of the natural felling direction. The ropes-assisted felling technique made all felled trees fall in the predetermined direction without producing barber chairs, but still causing hang-ups.